Exploring the T–Θ phase diagram of S adsorbed on Au(111) substrate on the Θ = 0.5 ML line - Gómez Carrillo, Sandra Carolina (2013)
Theoretical results for the adsorption of half of a monolayer of S on Au(111) are presented. The simulations were made using a density functional theory (DFT) tight binding approach combined with classical molecular dynamics at 800, 500, 300, 150 and 1 K. By considering a minimal $(2× \sqrt{3})$ unit cell, two stable adsorbed phases are found: a dimeric one and another forming a rhomboidal structure depending on the preparation of the sample at high temperatures. Optimized calculations at T = 0 K indicate that the stability of the dimeric phase is due to the increase of the binding energies between sulfur atoms. Enforcing previous results (Gómez-Carrillo et al 2011 Phys. Chem. Chem. Phys. 13 461) it is verified that at high temperatures (T > 300 K) sulfur atoms have a high mobility which allows migration among different adsorption sites. The mobility decreases with the temperature and, as in the previous work, a thermal barrier of 25–30 meV is found. On enlarging the unit cell new agglomerates are found, in good agreement with experimental data.